PENGARUH PEMBERIAN HADIAH TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK DARUL ISTIQOMAH NGUMPUL BALONG PONOROGO - Amrul Kanifah; Happy Susanto; Anip Dwi Saputra (TARBAWI:Journal on Islamic Education, 2020)
Al The success of a child's education will be achieved if the child has high motivation. When motivation arises in a child, will increase the spirit of curiosity about something. Therefore, there are many ways to motivate students to have a high enthusiasm in learning, namely by applying gifts in the learning process. This study aims to determine how the implementation of gift giving to students who are active in classroom learning and students who excel, and also to determine the effect of gift giving on student motivation in Islamic religious education subjects. This type of research is quantitative research. The subjects of this study were 53 students. The research method used is a mixed method, namely the interview method the author will know how the implementation of gift giving, and the questionnaire method is used to find out how the influence of gift giving on student motivation. To analyze the data, the authors use the SPSS 16 application. The results of this study can be concluded that giving prizes to students who are active while learning, the teacher gives it when learning too, so the teacher has prepared it before entering class. As for prizes for students who excel, prizes are given when distributing report cards after an exam. Meanwhile, the results of data processing by the author by giving gifts to students have an influence on student motivation. The influence of gift giving is 64.1%, while 35.9% of students' learning motivation is influenced by other factors not mentioned and revealed in this study.Keywords: Giving Gifts, Learning Motivation